Phase Equilibrium Studies of the CaO-MgO-Al2O3-SiO2 System for Iron Blast Furnace Slag: A Review - Jinfa Liao; Gele Qing; Baojun Zhao (Metals, 2023)
More and larger blast furnaces have been constructed for ironmaking across the world in recent years due to the advantages of high productivity, high energy efficiency and low cost. Slag plays important role in a blast furnace to produce high-quality hot metal and maintain smooth operations. Liquidus temperatures are the essential information of the slag to avoid the formation of the solid phase during the ironmaking process and slag tapping. The principal components of the iron blast furnace slags can be described by the system CaO-MgO-Al2O3-SiO2. With the significant changes in the raw materials and different requirements of the blast furnace operations, phase equilibria in this slag system have been extensively investigated from different directions. Phase diagrams were presented in various pseudo-ternary and pseudo-binary forms to meet the requirements of wide applications. Reliable thermodynamic modelling is the target of the researchers which can predict accurate liquidus temperatures of the slag. Development of the reliable thermodynamic modelling relies on systematic and accurate experimental data including liquidus temperatures and compositions of the solid solutions. Experimental data on the phase equilibria of the system CaO-MgO-Al2O3-SiO2 are summarised and compared with the thermodynamic predictions which can provide systematic information for the researchers and blast furnace operators.